Biografia pochwalna z 9 maja 1801 roku. Lektura kontekstowa - Dąbrowicz, Elżbieta (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
Comprehensive work on the history of nineteenth-century biographical texts has not been written yet and if it had, it would have to include the laudatory biographies practiced by Warsaw’s Towarzystwo Przyjaciół Nauk (Society of Friends of Arts and Sciences). An extensive collection of them can be found in their yearbooks. This article’s object of interest is Pochwała Józefa Szymanowskiego [Praise of Józef Szymanowski] by Stanisław Kostka Potocki, which was oftentimes cited as an example of exorbitant rhetoric in the past. Widely w Knidos [Venus temple in Knidos] casts shadow on TPN’s entire biographical work. The critics of the aforementioned Pochwała Józefa Szymanowskiego completely overlooked a substantial part of it which could be recognized as the founding story of the organization conceived in the Prussian part of the partitioned Poland; one that was taking its first shaky steps in uncertain times when the situation in Europe and the rest of the world was changing on a daily basis. commented unearned praise of the translation of Świątynia Wenery w Knidos [Venus temple in Knidos] casts shadow on TPN’s entire biographical work. The critics of the aforementioned Pochwała Józefa Szymanowskiego completely overlooked a substantial part of it which could be recognized as the founding story of the organization conceived in the Prussian part of the partitioned Poland; one that was taking its first shaky steps in uncertain times when the situation in Europe and the rest of the world was changing on a daily basis. changing on a daily basis.